2022
DOI: 10.3390/su14041945
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Sustainable Apparel Purchase Intention: An Empirical Study of Malaysian Millennial Consumers

Abstract: The fashion industry has expanded at the expense of the environment. Consumption and environmental pollution both serve as a wake-up call to the global endeavour to adopt more socially and environmentally responsible behaviours. It implies, in particular, a paradigm shift in consumer behaviour away from conventional to green products. Understanding the factors that influence consumer purchasing decisions is critical in developing the demand for and commitment to sustainable apparel consumption. In support of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 100 publications
1
24
0
4
Order By: Relevance
“…This means that sustainable consumption (SC) has made an important contribution in recent times in society, since consumers and customers have become aware of how important for the environment it is to buy environmentally friendly products, as studies such as [ 82 , 120 ] have shown. In the case of the Pacific Alliance countries, this study has demonstrated that by purchasing environmentally responsible products, a better culture of support for companies is built, and the consolidation of strategies that add value to brands for improved reputation is achieved, as concluded in prior studies [ 121 , 122 ]. This is how when mentioning sustainable consumption (SC), factors such as gender and demographic location, which influence the purchase decision, are taken into account.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This means that sustainable consumption (SC) has made an important contribution in recent times in society, since consumers and customers have become aware of how important for the environment it is to buy environmentally friendly products, as studies such as [ 82 , 120 ] have shown. In the case of the Pacific Alliance countries, this study has demonstrated that by purchasing environmentally responsible products, a better culture of support for companies is built, and the consolidation of strategies that add value to brands for improved reputation is achieved, as concluded in prior studies [ 121 , 122 ]. This is how when mentioning sustainable consumption (SC), factors such as gender and demographic location, which influence the purchase decision, are taken into account.…”
Section: Discussionmentioning
confidence: 55%
“…The era of sustainable products has impacted various sectors and the way in which they develop their production schemes, which gives the customer a better awareness in the responsible purchase of products that help the environment [ 121 ], thus consolidating culture in society. In addition, this allows companies to build an adequate brand reputation and become aspirational in the market [ 122 ] for the human talent that is part of the companies’ production processes, by providing motivating and consolidating work schemes that provide well-being and satisfaction to those who are part of the company [ 13 ], to build trust and achieve better articulation with business policies that support employees and customers [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…—Motivation (M), which can also be described as a goal-oriented incentive expressed by a person’s interest in and desire to do something; 55 …”
Section: Methodsmentioning
confidence: 99%
“…To anchor the theoretical background for our empirical study, one can draw upon the MOA framework to explain the determinants of whistleblowing behavior. Originally developed to understand consumer involvement in the processing of brand information and the corresponding purchasing behavior, the MOA framework asserts that behavior occurs through the confluence of three components: 54 -Motivation (M), which can also be described as a goal-oriented incentive expressed by a person's interest in and desire to do something; 55 -Opportunity (O), which is defined as external factors that prompt or inhibit the occurrence of the behavior, namely, the conditions that affect a person's attentiveness, whether favorable or not; 56 and…”
Section: Research Design Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…Reliable, all of that is part of the behavior that the millennial generation must have. Various studies on environmental and greenery issues continue to be held here and there to explore how the mental qualities of millennial children to the older generation can positively impact their participation in a healthy environment (Hasbullah et al, 2022). Because it is believed that the involvement of the younger generation, such as millennials, will undoubtedly have a significant impact because, in the future, they will become the parties who become policy makers both in practice, whether government, business, community, or even individuals to see to what extent the role of the young millennial generation in participation weakens the earth like create a revolution and design laws whose purpose is environmental protection, study after study must continue to be encouraged in order to be able to issue various recommendations and conclusions which in the end is for the sake of saving, continuing, healthy and sustainable environmental sustainability (Ogamba, 2018).…”
Section: Introductionmentioning
confidence: 99%